Detection of food additives by voltammetry at the liquid-liquid interface - Herzog, G.; KAM, V.; Berduque, A.; Arrigan, Damien (American Chemical Society, 2008)
Electrochemistry at the liquid-liquid interface enables the detection of nonredoxactive species withelectroanalytical techniques. In this work, the electrochemical behavior of two food additives, aspartameand acesulfame K, was investigated. Both ions were found to undergo ion-transfer voltammetry at the liquid-liquid interface. Differential pulse voltammetry was used for the preparation of calibration curves over the concentration range of 30-350 µM with a detection limit of 30 µM. The standard addition method was applied to the determination of their concentrations in food and beverage samples such as sweeteners and sugar-free beverages. Selective electrochemically modulated liquid-liquid extraction of these species in both laboratory solutions and in beverage samples was also demonstrated. These results indicate the suitability of liquid-liquid electrochemistry as an analytical approach in food analysis.